Graphene oxide and sodium alginate composite membrane for extracting ocean osmotic energy and preparation method of graphene oxide and sodium alginate composite membrane

Through the composite film technology of graphene oxide and sodium alginate, the stability and cost problems of high-power density films in the prior art are solved, and the marine permeability energy extraction with high power density and high stability is achieved, providing a feasible solution for commercial applications.

CN119524638AActive Publication Date: 2025-02-28HAINAN UNIV

Patent Information

Application Number
CN202411882090.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

In the prior art, when developing high power density ion selective films, it is difficult to achieve high stability and low cost at the same time, and there are limited methods to regulate surface charge density, making it difficult to obtain extremely high surface charge density.

Method used

The graphene oxide and sodium alginate composite film is used to fully cross-link the graphene oxide nanosheets and the sodium alginate molecular chain through electromagnetic stirring to form a dense cross-linking network to improve the space charge distribution characteristics of the film.

Benefits of technology

A high power density (approximately 14.75 W/m² at 50 times NaCl concentration gradient and 20.94 W/m² at 50 times KCl concentration gradient) and high stability composite membranes are achieved, while reducing production costs and providing a feasible solution for commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524638A_ABST
    Figure CN119524638A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy. The preparation method specifically comprises the following steps: step 1, preparing a sodium alginate solution; step 2, preparing a graphene oxide solution; 3, putting the sodium alginate solution into the graphene oxide solution, and carrying out electromagnetic stirring to obtain a mixed dispersion liquid; step 4, taking a polycarbonate film, taking the polycarbonate film as a substrate, putting the polycarbonate film into a trace suction flask, taking the mixed dispersion liquid, and performing vacuum suction filtration on the mixed dispersion liquid in the trace suction flask to obtain a polycarbonate film covered with a graphene oxide sodium alginate composite film; step 5, stripping the polycarbonate film covered with the graphene oxide and sodium alginate composite film, and naturally drying to obtain the graphene oxide and sodium alginate composite film for extracting the ocean osmotic energy. The invention further discloses the graphene oxide and sodium alginate composite membrane for extracting the ocean osmotic energy. The prepared composite membrane has the advantages of being high in power density, good in stability and high in economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of development of ocean salinity difference energy, relates to a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy, and also relates to a method for preparing the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy. Background Art

[0002] In recent years, with the global awareness of the urgency of mitigating the climate crisis caused by fossil fuel consumption, the exploration of sustainable and renewable energy has gathered into an unprecedented powerful force. Among the many emerging technology waves, reverse electrodialysis (RED) technology has emerged as a cutting-edge means to tap the huge potential of salinity gradient power generation in natural environments such as the ocean. The core of RED system performance lies in the research and development of high-power density membranes. This field continues to attract extensive attention and in-depth exploration in the scientific research community, aiming to continuously optimize the ion selectivity, durability and cost-effectiveness of the membrane. Particularly noteworthy is that two-dimensional (2D) materials such as graphene oxide (GO) and MXenes, with their unique structural characteristics and excellent chemical properties, have shown extraordinary potential and excellent performance in the field of salinity gradient energy conversion, injecting new vitality and hope into the development of RED technology.

[0003] Graphene oxide (GO) is an important derivative of graphene and is the product obtained after graphene undergoes oxidation reaction. Its surface and edges contain a large number of oxygen-containing groups, such as hydroxyl, epoxy, carboxyl and carbonyl. These groups enable graphene oxide to provide extremely rich surface charges when used as nanochannel materials, thereby obtaining extremely high ion selectivity. It has also been proven to be an effective means to regulate the surface charge of nanochannels to obtain higher osmotic energy conversion power. Huang's team found that it is easy to form an unprecedented large number of nanochannel arrays by restacking the peeled graphene oxide sheets, and also confirmed that graphene oxide is a two-dimensional material for the ideal platform for nanofluid ion transport. Jiang's team effectively changed the surface charge polarity of graphene oxide nanochannels through pre-assembly modification, producing graphene oxide membranes with strong cation or anion selectivity, and obtained an osmotic energy conversion (OEC) power density that is about 54% higher than that of commercial ion exchange membranes. Lei's team used the self-stripping behavior of graphene oxide substrate plane oxidized fragments in an alkaline environment to encapsulate the separated oxidized fragments in nanochannels to increase the OEC power density from 1.8 W / m 2 Increased to 4.9 W / m 2. In addition, the surface charge density of the membrane can also be regulated by adjusting the temperature, pH, light and other conditions of the environment, thereby improving the osmotic energy conversion efficiency. However, the promotion effect brought by regulating the surface charge density is limited, and it is difficult to obtain an extremely high surface charge density, which requires us to find new methods. Cao's team cut off the ultra-thick graphene oxide membrane, used the cross section as the permeation surface, and changed the ion transmission pathway to achieve a high efficiency of up to 10.6W / m 2 Ultra-high power density can be achieved, but this method still has great limitations due to the difficulty in obtaining large cross-sections. In order to more effectively obtain high power density of osmotic energy conversion, researchers have found through numerical simulation that the synergistic effect of surface charge and space charge in nanochannels can achieve higher osmotic energy conversion power, which has been confirmed in many related experiments. This theory provides a new idea for the design of ion-selective membranes. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy. The composite membrane prepared by the method has the characteristics of high power density, good stability and high economic value.

[0005] Another object of the present invention is to provide a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy.

[0006] The first technical solution adopted by the present invention is a method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy, which specifically comprises the following steps: Step 1, preparing a sodium alginate solution; Step 2, preparing a graphene oxide solution; Step 3, placing the sodium alginate solution prepared in step 1 into the graphene oxide solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a microfiltration bottle, taking the mixed dispersion in the microfiltration bottle for vacuum filtration, and obtaining a polycarbonate membrane covered with a graphene oxide sodium alginate composite membrane; Step 5: peeling off the graphene oxide sodium alginate composite membrane from the polycarbonate membrane covered with the graphene oxide sodium alginate composite membrane, and drying naturally to obtain the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy.

[0007] The first technical solution of the present invention is also characterized in that: The specific process of step 1 is: Step 1.1, take deionized water into the reactor and take a certain amount of sodium alginate; Step 1.2, dissolving sodium alginate in deionized water, and fully dissolving it by electromagnetic stirring to obtain a sodium alginate solution.

[0008] The concentration of the sodium alginate solution in step 1 is 1-20 mg / ml.

[0009] The concentration of the graphene solution in step 1 is 0.1-5 mg / ml.

[0010] The specific process of step 2 is: Step 2.1, taking a certain amount of graphene oxide into another reactor and taking deionized water; Step 2.2, adding deionized water to the graphene oxide for dilution to obtain a graphene oxide solution.

[0011] In step 3, the volume of the sodium alginate solution added is not greater than the volume of the graphene oxide solution.

[0012] In step 3, the rotation speed of the electromagnetic stirring is 800-1200 r / min, and the time of the electromagnetic stirring is 6-24 h.

[0013] The time of vacuum filtration in step 4 is 5-7 days.

[0014] The natural drying time in step 5 is 8-24h.

[0015] The second technical solution adopted by the present invention is that the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy is prepared by adopting the preparation method of the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy.

[0016] The beneficial effects of the present invention are as follows: The graphene oxide sodium alginate composite membrane and preparation method for extracting ocean osmotic energy provided by the present invention cleverly utilize the two-dimensional layered framework formed by stacking graphene oxide nanosheets as a stable foundation, and sodium alginate, a polysaccharide widely present in nature, is rich in negatively charged functional groups that weave a dense cross-linked network between the nanosheets, giving the membrane excellent spatial charge distribution characteristics. This unique design concept not only greatly enhances the ion selectivity of the membrane, but also achieves a significant increase in power density in RED applications. Under a 50-fold NaCl concentration gradient, the composite membrane exhibits an excellent power density of about 14.75 W / m²; and under a 50-fold KCl concentration gradient, its power density soars to 20.94 W / m², a value that far exceeds the industry-recognized 5.0 W / m² baseline. Even more remarkable is that the economic feasibility of the membrane is also outstanding. Its raw materials are mainly sodium alginate, supplemented by graphene oxide, which are low-cost and environmentally friendly. In addition, the simple manufacturing process has built a solid foundation for large-scale commercial applications, indicating a broad market prospect. This invention is not only an innovative achievement of high-performance salinity gradient energy conversion membrane technology in the RED field, but also provides a new design idea and strategy for the development and utilization of marine salinity gradient energy. By demonstrating the balance between cost-effectiveness and power density, our work has created more possibilities for the practical application of marine salinity gradient energy, and has strongly promoted the world to move towards a greener and more sustainable energy future. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic flow diagram of a method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy according to the present invention; Figure 2 is a scanning electron microscope image of the surface of the pure graphene oxide film in Example 6 of the present invention; Figure 3 is a scanning electron microscope image of the surface of the graphene oxide sodium alginate composite film in Example 6 of the present invention; Figure 4 is a stress-strain curve diagram of the pure graphene oxide film and the graphene oxide sodium alginate composite film in Example 6 of the present invention; Figure 5 It is a Zeta potential diagram of pure graphene oxide dispersion, sodium alginate solution and graphene oxide sodium alginate mixed dispersion under different pH environments in Example 6 of the present invention; Figure 6 is an X-ray diffraction pattern of the pure graphene oxide film and the graphene oxide sodium alginate composite film in Example 6 of the present invention; Figure 7 This is a graph of the volt-ampere characteristic of the composite membrane under a 1000-fold KCl concentration gradient in Example 6 of the present invention; Figure 8is a schematic diagram showing the shift of transmembrane conductance compared to bulk conductance at different KCl concentrations in Example 6 of the present invention; Fig. 9 is a graph showing the current variation of the composite film in 0.1M KCl solution of different pH values ​​under the action of a periodic voltage of -0.1V to 0.1V in Example 6 of the present invention; Fig.10 is a graph showing the change in current density of the graphene oxide sodium alginate composite membrane with external load under different parameter ratios in Example 6 of the present invention; Fig.11 is a graph showing the power density of the graphene oxide sodium alginate composite film changing with the external load under different parameter ratios in Example 6 of the present invention; Fig.12 is a curve diagram showing the power density of the graphene oxide sodium alginate composite membrane in artificial seawater and natural seawater as a function of the external load in Example 6 of the present invention; Fig.13 This is a statistical result diagram of the maximum power density of graphene oxide sodium alginate composite films of different thicknesses in Example 6 of the present invention; Fig.14 is a bar graph of the maximum power density of the graphene oxide film and the graphene oxide sodium alginate composite film in Example 6 of the present invention in NaCl solutions with different concentration gradients; Fig.15 is a bar graph of power density of the graphene oxide sodium alginate composite film in Example 6 of the present invention in different electrolyte solutions with a concentration gradient of 50 times; Fig.16 It is a bar graph of the maximum power density of the graphene oxide sodium alginate composite film at different test areas under a 1000-fold NaCl solution concentration gradient in Example 6 of the present invention; Fig.17 is a comparison diagram of power density between the present application and the prior art in Example 6 of the present invention; Fig.18 is a bar graph showing the maximum power density variation of the graphene oxide sodium alginate composite film in Example 6 of the present invention at different pH values ​​and pH gradients; Fig.19 is a bar graph of current density variation when the graphene oxide sodium alginate composite film in Example 6 of the present invention reaches the maximum power density; Fig. 20 is a bar graph showing the maximum power density variation of the graphene oxide film in Example 6 of the present invention at different pH values ​​and pH gradients; Fig.21 is a bar graph of current density variation when the graphene oxide film in Example 6 of the present invention reaches the maximum power density; Fig. 22is a schematic diagram of axial cation concentration of a nanochannel model under different spatial charge densities in Example 6 of the present invention; Fig.23 is a graph showing the axial anion concentration distribution of the nanochannel model under different spatial charge densities in Example 6 of the present invention; Fig.24 is a histogram of anion and cation fluxes of the nanochannel model under different spatial charge densities in Example 6 of the present invention; Fig.25 is a radial cation concentration distribution diagram of the nanochannel model at different channel radii in Example 6 of the present invention; Fig.26 is a radial anion concentration distribution diagram of the nanochannel model at different channel radii in Example 6 of the present invention; Fig. 27 It is a bar chart of anion and cation fluxes of the nanochannel model at different channel radii in Example 6 of the present invention. DETAILED DESCRIPTION

[0018] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0019] The preparation method of the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing a sodium alginate solution; The specific process is: Step 1.1, take deionized water into the reactor and take a certain amount of sodium alginate; Step 1.2, dissolving sodium alginate in deionized water, and fully dissolving it by electromagnetic stirring to obtain a sodium alginate solution; the solution is light yellow and has a certain viscosity; The concentration of sodium alginate solution is 1-20 mg / ml; the concentration of graphene solution is 0.1-5 mg / ml; Step 2, preparing a graphene oxide solution; The specific process is: Step 2.1, taking a certain amount of graphene oxide into another reactor and taking deionized water; Step 2.2, adding deionized water to the graphene oxide for dilution to obtain a graphene oxide solution; Step 3, placing the sodium alginate solution prepared in step 1 into the graphene oxide solution prepared in step 2, and fully dissolving it by electromagnetic stirring, so that the graphene oxide nanosheets and the sodium alginate molecular chains are fully cross-linked to obtain a mixed dispersion; the mixed dispersion has a certain viscosity, and as the content of the sodium alginate solution increases, the viscosity gradually increases; The speed of electromagnetic stirring is 800-1200r / min, and the time of electromagnetic stirring is 6-24h; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a microfiltration bottle, taking the mixed dispersion in the microfiltration bottle for vacuum filtration, and obtaining a polycarbonate membrane covered with a graphene oxide sodium alginate composite membrane; the vacuum filtration time is 5-7 days; Step 5: peel off the graphene oxide sodium alginate composite membrane and the polycarbonate membrane in the polycarbonate membrane covered with the graphene oxide sodium alginate composite membrane, and dry naturally to obtain the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy; the natural drying time is 8-24 hours.

[0020] Since the main component of the composite membrane is sodium alginate, and sodium alginate cannot form a membrane alone, the stable structure of the composite membrane benefits from the stacking of graphene oxide. When the sodium alginate component in the mixed dispersion is too high, the membrane structure will be unstable, and a higher sodium alginate content will greatly increase the viscosity of the mixed dispersion, increase the film-forming cycle of the vacuum filtration, reduce the efficiency of the film-making cycle, and even cause blockage, so that the vacuum filtration cannot be completed. Therefore, the volume of the sodium alginate solution added in step 3 is not greater than the volume of the graphene oxide solution.

[0021] Example 1 The preparation method of the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing a sodium alginate solution; Step 2, preparing a graphene oxide solution; Step 3, placing the sodium alginate solution prepared in step 1 into the graphene oxide solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a microfiltration bottle, taking the mixed dispersion in the microfiltration bottle for vacuum filtration, and obtaining a polycarbonate membrane covered with a graphene oxide sodium alginate composite membrane; Step 5: peeling off the graphene oxide sodium alginate composite membrane from the polycarbonate membrane covered with the graphene oxide sodium alginate composite membrane, and drying naturally to obtain the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy.

[0022] Example 2 The preparation method of the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing a sodium alginate solution; The specific process of step 1 is: Step 1.1, take deionized water into the reactor and take a certain amount of sodium alginate; Step 1.2, dissolving sodium alginate in deionized water, and fully dissolving it by electromagnetic stirring to obtain a sodium alginate solution; In step 1, the concentration of the sodium alginate solution is 1-20 mg / ml; In step 1, the concentration of the graphene solution is 0.1-5 mg / ml; Step 2, preparing a graphene oxide solution; The specific process of step 2 is: Step 2.1, taking a certain amount of graphene oxide into another reactor and taking deionized water; Step 2.2, adding deionized water to the graphene oxide for dilution to obtain a graphene oxide solution; Step 3, placing the sodium alginate solution prepared in step 1 into the graphene oxide solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a microfiltration bottle, taking the mixed dispersion in the microfiltration bottle for vacuum filtration, and obtaining a polycarbonate membrane covered with a graphene oxide sodium alginate composite membrane; Step 5: peeling off the graphene oxide sodium alginate composite membrane from the polycarbonate membrane covered with the graphene oxide sodium alginate composite membrane, and drying naturally to obtain the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy.

[0023] Example 3 The preparation method of the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing a sodium alginate solution; The specific process of step 1 is: Step 1.1, take deionized water into the reactor and take a certain amount of sodium alginate; Step 1.2, dissolving sodium alginate in deionized water, and fully dissolving it by electromagnetic stirring to obtain a sodium alginate solution; In step 1, the concentration of the sodium alginate solution is 1-20 mg / ml; In step 1, the concentration of the graphene solution is 0.1-5 mg / ml; Step 2, preparing a graphene oxide solution; The specific process of step 2 is: Step 2.1, taking a certain amount of graphene oxide into another reactor and taking deionized water; Step 2.2, adding deionized water to the graphene oxide for dilution to obtain a graphene oxide solution; Step 3, placing the sodium alginate solution prepared in step 1 into the graphene oxide solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; In step 3, the volume of the sodium alginate solution added is not greater than the volume of the graphene oxide solution; In step 3, the speed of electromagnetic stirring is 800-1200 r / min, and the time of electromagnetic stirring is 6-24 h; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a microfiltration bottle, taking the mixed dispersion in the microfiltration bottle for vacuum filtration, and obtaining a polycarbonate membrane covered with a graphene oxide sodium alginate composite membrane; Step 5: peeling off the graphene oxide sodium alginate composite membrane from the polycarbonate membrane covered with the graphene oxide sodium alginate composite membrane, and drying naturally to obtain the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy.

[0024] Example 4 The preparation method of the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing a sodium alginate solution; The specific process of step 1 is: Step 1.1, take deionized water into the reactor and take a certain amount of sodium alginate; Step 1.2, dissolving sodium alginate in deionized water, and fully dissolving it by electromagnetic stirring to obtain a sodium alginate solution; In step 1, the concentration of the sodium alginate solution is 1-20 mg / ml; In step 1, the concentration of the graphene solution is 0.1-5 mg / ml; Step 2, preparing a graphene oxide solution; The specific process of step 2 is: Step 2.1, taking a certain amount of graphene oxide into another reactor and taking deionized water; Step 2.2, adding deionized water to the graphene oxide for dilution to obtain a graphene oxide solution; Step 3, placing the sodium alginate solution prepared in step 1 into the graphene oxide solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; In step 3, the volume of the sodium alginate solution added is not greater than the volume of the graphene oxide solution; In step 3, the speed of electromagnetic stirring is 800-1200 r / min, and the time of electromagnetic stirring is 6-24 h; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a microfiltration bottle, taking the mixed dispersion in the microfiltration bottle for vacuum filtration, and obtaining a polycarbonate membrane covered with a graphene oxide sodium alginate composite membrane; The time of vacuum filtration in step 4 is 5-7 days; Step 5: peeling off the graphene oxide sodium alginate composite membrane from the polycarbonate membrane covered with the graphene oxide sodium alginate composite membrane, and drying naturally to obtain the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy.

[0025] Example 5 The preparation method of the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing a sodium alginate solution; The specific process of step 1 is: Step 1.1, take deionized water into the reactor and take a certain amount of sodium alginate; Step 1.2, dissolving sodium alginate in deionized water, and fully dissolving it by electromagnetic stirring to obtain a sodium alginate solution; In step 1, the concentration of the sodium alginate solution is 1-20 mg / ml; In step 1, the concentration of the graphene solution is 0.1-5 mg / ml; Step 2, preparing a graphene oxide solution; The specific process of step 2 is: Step 2.1, taking a certain amount of graphene oxide into another reactor and taking deionized water; Step 2.2, adding deionized water to the graphene oxide for dilution to obtain a graphene oxide solution; Step 3, placing the sodium alginate solution prepared in step 1 into the graphene oxide solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; In step 3, the volume of the sodium alginate solution added is not greater than the volume of the graphene oxide solution; In step 3, the speed of electromagnetic stirring is 800-1200 r / min, and the time of electromagnetic stirring is 6-24 h; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a microfiltration bottle, taking the mixed dispersion in the microfiltration bottle for vacuum filtration, and obtaining a polycarbonate membrane covered with a graphene oxide sodium alginate composite membrane; The time of vacuum filtration in step 4 is 5-7 days; Step 5, peeling off the graphene oxide sodium alginate composite membrane and the polycarbonate membrane in the polycarbonate membrane covered with the graphene oxide sodium alginate composite membrane, and drying naturally to obtain the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy; The natural drying time in step 5 is 8-24h.

[0026] Example 6 The preparation method of the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy of the present invention is as follows: Figure 1 As shown, the specific steps include: Step 1, preparing a sodium alginate solution; The specific process of step 1 is: Step 1.1, take deionized water into the reactor and take a certain amount of sodium alginate; Step 1.2, dissolving sodium alginate in deionized water, and fully dissolving it by electromagnetic stirring to obtain a sodium alginate solution; The concentration of the sodium alginate solution in step 1 is 10 mg / ml; the concentration of the graphene solution in step 1 is 0.1 mg / ml; Step 2, preparing a graphene oxide solution; The specific process of step 2 is: Step 2.1, taking a certain amount of graphene oxide into another reactor and taking deionized water; Step 2.2, adding deionized water to the graphene oxide for dilution to obtain a graphene oxide solution; Step 3, putting the sodium alginate solution prepared in step 1 into the graphene oxide solution prepared in step 2, mixing with the sodium alginate solution at a ratio of 40 ml: x ml, and fully dissolving it by electromagnetic stirring, so that the graphene oxide nanosheets and the sodium alginate molecular chains are fully cross-linked to obtain a mixed dispersion; the mixed dispersion has a certain viscosity, and as the content of the sodium alginate solution increases, the viscosity gradually increases; The volume of the sodium alginate solution added in step 3 is not greater than the volume of the graphene oxide solution; the speed of the electromagnetic stirring in step 3 is 900 r / min, and the time of the electromagnetic stirring is 24 h; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a microfiltration bottle, taking the mixed dispersion in the microfiltration bottle for vacuum filtration, and obtaining a polycarbonate membrane covered with a graphene oxide sodium alginate composite membrane; The time of vacuum filtration in step 4 is 7 days; Step 5, peeling off the graphene oxide sodium alginate composite membrane and the polycarbonate membrane in the polycarbonate membrane covered with the graphene oxide sodium alginate composite membrane, and drying naturally to obtain the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy; the natural drying time in step 5 is 24 hours.

[0027] Since the main component of the composite membrane is sodium alginate, and sodium alginate cannot form a membrane alone, the stable structure of the composite membrane benefits from the stacking of graphene oxide. When the sodium alginate content in the mixed dispersion is too high, the membrane structure will be unstable, and the higher sodium alginate content will greatly increase the viscosity of the mixed dispersion, increase the film-forming cycle of the vacuum filtration, reduce the efficiency of the film-making cycle, and even cause blockage, so that the vacuum filtration cannot be completed. Therefore, in the mixing ratio of the mixed dispersion in this application (40ml: xml), x≤40.

[0028] like Figure 4 As shown in the figure, the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy has certain light transmittance and good mechanical properties. When the composite membrane is immersed in real seawater, the volume of the composite membrane expands but the shape remains. Figure 2 As shown in Figure 2, under SEM scanning electron microscopy, the surface of pure graphene oxide membrane is relatively flat, and the typical stacking structure of two-dimensional layered membrane can be observed in the cross section, while the surface of graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy has many spherical substances, such as Figure 3 As shown, obvious material doping between the layered structures can also be observed in the cross section. Through the EDS graph, the elements on the surface and cross section of the composite membrane are evenly distributed, which shows that sodium alginate (SA) and graphene oxide (GO) are fully mixed and the composite membrane structure is uniform. Further analysis combined with the XPS graph shows that the intensity of CC=O in the composite membrane is significantly increased relative to the pure GO membrane, which further illustrates the full combination of sodium alginate and graphene oxide nanosheets. The composite membrane exhibits excellent performance in the process of osmotic energy conversion, which is directly related to the surface charge density and channel pore size of the ion transport nanochannels in the composite membrane. Figure 5 As shown in the figure, by measuring the Zeta potential of the mixed dispersion, it can be found that the mixed dispersion has the maximum Zeta potential in an alkaline environment. The Zeta potential of the mixed dispersion shows a trend of increasing first and then decreasing with the increase of sodium alginate content, reaching the maximum at x=25, which means that the surface charge density of the composite film reaches the maximum value near the parameter ratio of x=25. At the same time, Figure 6 As shown in the figure, by analyzing the XRD of composite membranes with different parameter ratios, it can be found that as the content of sodium alginate increases, the highest peak of the XRD graph gradually shifts to the left, which indicates that the interlayer spacing of the composite membrane gradually increases. Combined with the conductivity values ​​of composite membranes with different parameter ratios, when x=30, the composite membrane has a larger surface charge density, a larger interlayer spacing and a maximum conductivity. We believe that this is the fundamental reason why the composite membrane with this parameter ratio has the best osmotic energy conversion performance. As the content of sodium alginate increases, the hydrophobicity of the composite membrane surface increases, which may also be one of the reasons for the increase in the power density of the composite membrane. The ion transmission area of ​​the composite membrane is controlled by using a perforated silicon wafer, and the perforated area of ​​the silicon wafer is 3x10-8 m 2 , the ion transport properties of the hybrid membrane were studied by monitoring the transmembrane ion current. Figure 7 As shown in the figure, 0.5M and 0.01M NaCl solutions were used as artificial seawater and river water to carry out experiments, and the composite membrane with a reference ratio (x=20) was used as the experimental object. KCl solution with a concentration gradient of 1000 times was added to both ends of the composite membrane to test the IV change curve of the composite membrane. After reversing the concentration gradient, the test was repeated. The two IV curves of the composite membrane were approximately parallel, indicating that the composite membrane has good symmetry. In addition, Figure 8 As shown in the figure, the experiment tested the changes in the transmembrane conductance of the composite membrane under the action of different concentrations of KCl solution. When the electrolyte concentration is <0.01 M, the transmembrane conductance obviously deviates from the bulk value (red dotted line), indicating that the transport of ions through the composite membrane is mainly controlled by the surface charge of the membrane. Fig. 9 As shown in the figure, 0.1M KCl solution with different pH values ​​was selected as the background solution, and the current change curve was tested under the action of periodic voltage from -0.1V to 0.1V. The transmembrane current and voltage changes showed consistency, and the current size did not change significantly, indicating that the composite membrane has a certain stability under the three pH environments.

[0029] like Fig.10 As shown in the figure, the salt difference power generation current density and power density of the GO / SA composite membrane under different parameter ratios were tested in the experiment. When x = 30, the GO / SA composite membrane has the maximum current density under different loads, as shown in Fig.11 As shown in Figure 2, the power generation density of the GO-SA composite membrane reaches a maximum value of about 14.75 W / m when the external load is about 7000 Ω. 2 ,like Fig.17 The current industry standard (5W / m 2 ), far exceeding the power density reported by most existing materials. Fig.12 As shown in Figure 2, under the action of natural seawater and artificial river water, the power density of the composite membrane is as high as 19.39W / m 2. By observing the power density of the composite membrane under different parameter ratios and the curve of the external load, it is not difficult to find that the composite membrane with a greater power density reaches the maximum value under a lower external load, which shows that the cross-linking of sodium alginate and graphene oxide nanosheets greatly changes the resistance of the GO-SA composite membrane. By measuring the IV curve of the composite membrane under an external voltage of -0.2V-0.2V and calculating the conductivity of the composite membrane, the composite membrane has the maximum conductivity when x=30. At the same time, by analyzing the Zeta potential of the mixed dispersions with different parameter ratios, it is found that the cross-linking of sodium alginate and graphene oxide nanosheets will greatly increase the Zeta potential of the mixed dispersion, which will make the nanochannels of the GO-SA composite membrane have a larger surface charge, thereby increasing the ion selectivity of the composite membrane. Therefore, when x=30, the composite membrane has a larger surface charge density and a higher ion selectivity. At the same time, the composite membrane has a larger interlayer spacing, which leads to a larger conductivity of the composite membrane, so that the composite membrane has a larger ion flux, thereby obtaining a higher power density. In addition, we conducted continuous measurements of composite membranes with different parameter ratios under an external load of 13000Ω for 90 minutes, and took experimental data every 5 minutes for result analysis. We found that the power density and current density of the composite membrane were relatively stable, which shows that the composite membrane has a certain stability.

[0030] The experiment also tested the relationship between the power density of the composite membrane with the best parameter ratio and the membrane thickness under different membrane thicknesses. We obtained composite membranes of different thicknesses by vacuum filtration of mixed dispersions of different volumes. We cut the obtained composite membranes into pieces with an area of ​​about 0.25 cm 2 The thickness of each film was measured by a thickness gauge, and the film thickness was roughly divided into five groups: 30um, 40um, 50um, 60um, and 70um. Each group of films was tested, and 9 sets of data were obtained for each group for statistical analysis. The experimental results show that Fig.13 As shown in the figure, the maximum power density can be obtained when the film thickness is about 50um. Under the concentration gradient of 50 times NaCl solution, the average power density is as high as 15.82W / m 2 , which is much higher than most of the reported materials. In addition, the parameter ratio composite membrane (x=30) with the maximum power density under 50 times NaCl concentration gradient was used as the experimental object, such as Fig.14 As shown in the figure, the power density and current density of the composite membrane under different NaCl concentration gradients were tested as a function of external load. The composite membrane has a power density of up to 50.59 W / m at a concentration gradient of 500 times. 2 In addition, the composite membrane was tested under a 50-fold concentration gradient, such as Fig.15 As shown in Figure 2, the power density and current density in different electrolyte solutions vary with external load. The composite membrane has the highest power density in KCl solution, which is 20.94 W / m 2, in LiCl, MgCl 2 and CaCl 2 With 13.17W / m 2 , 9.19W / m2, 6.75W / m 2 The power density of the product is excellent, and all data show excellent performance. Fig.16 As shown in Figure 2, unfortunately, the power generation performance of the composite membrane dropped sharply under large-area testing. Under a 1000-fold NaCl solution concentration gradient, the test area was expanded to 0.25 mm 2 When the power density is only 7.85W / m 2 .

[0031] Sodium alginate has obvious pH sensitivity. Under acidic conditions, -COO - It turns into -COOH, the degree of ionization decreases, the hydrophilicity of sodium alginate decreases, the molecular chain shrinks, and when the pH value increases, the -COOH group continuously dissociates, the hydrophilicity of sodium alginate increases, and the molecular chain stretches. In an environment with pH=3, the surface charge density of the GO / SA composite membrane is at a low level. In addition, due to the shrinkage of the sodium alginate molecular chain, the spatial charge density in the composite membrane is also at a low level, which leads to low ion selectivity and low power density of the composite membrane. When the high concentration end pH=3 and the low concentration end pH=11, the surface charge density inside the composite membrane increases, and at the same time, the sodium alginate molecular chain stretches and the spatial charge density increases, thereby improving the ion selectivity of the composite membrane and increasing the power density. In addition, due to the H + The concentration difference is large, and the power density is further improved under the drive of chemical potential. In the environment of pH=11, the surface charge density and space charge density in the composite membrane reach the maximum value, which also makes the composite membrane have the maximum power density. Therefore, the composite membrane also has different power generation performance under different pH environments. The experimental results show that Fig.18 As shown in the figure, the power density of the composite membrane is the highest in an alkaline environment, which is 19.7% higher than that in a neutral environment, while the power density of the composite membrane is the lowest in an acidic environment, which is 35.1% lower than that in a neutral environment. Fig.19 As shown in Fig. 4B, when the composite membrane reaches the maximum power density, its current density changes follow the same law. Fig. 20 , 21 As shown in the figure, the power density and current density of pure graphene oxide membrane under different pH environments were tested as a control. Although the power generation performance of the composite membrane under acidic conditions is far inferior to that under alkaline conditions, it still has a high current density of 8.14W / m 2 The power density experiment was also tested with pure graphene oxide membrane under different pH conditions as a control. In summary, the composite membrane also has great application potential in obtaining osmotic energy from acidic or alkaline wastewater.

[0032] The GO-SA composite membrane uses the two-dimensional layered structure of graphene oxide membrane as the framework and sodium alginate as the filler. The two are cross-linked by hydrogen bonds to form a stable nanochannel structure. We simplified the nanochannel structure and conducted research based on the cylindrical nanochannel model.

[0033] When the amount of cross-linking between sodium alginate and graphene oxide is small, the spatial charge density in the nanochannel is low. As the sodium alginate parameter increases, the spatial charge content in the nanochannel increases. Through numerical model analysis, we found that when the surface charge density is the same, the increase in the spatial charge density in the nanochannel can increase the diffusion current and diffusion voltage, thereby increasing the power generation of the nanopore. And, Fig. 22 As shown in Figure 2, in the axial direction of the nanochannel, the larger space charge density makes the cations in the nanochannel enriched, such as Fig.23 As shown, the anions dissipate, giving the nanochannel greater ion selectivity. In addition, when the solution pH increases, the surface charge density of the nanochannel will increase, and the increase in surface charge density will work synergistically with the space charge to further increase the ion selectivity of the nanochannel, thereby obtaining a greater salt difference power generation power, which is one of the reasons why the composite membrane has a very large power density in an alkaline environment.

[0034] When sodium alginate is cross-linked with graphene oxide, the spatial charge in the nanochannel increases, accompanied by an increase in the interlayer spacing of the composite membrane. The study first set the nanochannel radius at 2-6nm. Through numerical model analysis, when the surface charge density remains unchanged and the nanochannel radius increases, the salt difference power generation power of the nanochannel first increases and then decreases, reaching a maximum value when the channel radius is about 3-4nm. Further analysis shows that with the increase of the channel radius, the diffusion current in the nanochannel increases, but the ion selectivity gradually decreases, which makes the diffusion voltage in the nanochannel significantly decrease, resulting in the power generation power first increasing and then decreasing. Combined with the relevant experimental results of the composite membrane, with the increase of sodium alginate content, the interlayer spacing of the composite membrane increases, and the power density gradually increases, reaching a maximum value at x=30. Therefore, when studying the mechanism of the increase in the power density of the composite membrane, the channel radius of the numerical model should be controlled below 3nm. It is worth mentioning that when the nanochannel radius is within 2.0~2.4nm, such as Fig.25 , 26 As shown, the concentration changes of cations and anions in the nanochannel are small, and mainly manifested at the low concentration end. This is related to the change in the thickness of the double electric layer in the nanochannel, which is also the main reason for the change in the ion selectivity of the nanochannel.

[0035] From the perspective of ion flux, we compared and analyzed the effects of space charge change and channel radius change. We found that Fig.24As shown, with the increase of space charge density, the cation flux in the nanochannel increases while the anion flux decreases, as shown in Fig. 27 As shown in the figure, with the increase of channel radius, the cation flux and anion flux in the nanochannel gradually increase. Therefore, when sodium alginate and graphene oxide are cross-linked to increase the space charge and interlayer spacing at the same time, the effect of space charge will reduce the increase in anion flux caused by the increase in interlayer spacing, which will keep the ion selectivity of the nanochannel at a high level. At the same time, the nanochannel has a large ion flux. Under the combined influence, the nanochannel has a huge diffusion current, thereby obtaining an extremely high salt difference power generation power.

[0036] In summary, the surface functional groups of graphene oxide provide a large amount of surface charge, while sodium alginate provides a large amount of space charge between the layers. The surface charge and space charge work together to make the composite membrane have excellent ion selectivity. At the same time, sodium alginate and graphene oxide are cross-linked to expand the distance between the two-dimensional membrane layers and the ion transmission channel, which makes the composite membrane have a larger ion flux. With better ion selectivity and greater ion flux, the composite membrane can generate a larger permeation current under a certain salinity gradient, making the power density of the composite membrane far exceed that of pure graphene oxide membrane. At the same time, the composite membrane uses graphene oxide nanosheets as the basic framework and sodium alginate as the main filler. The raw materials are mainly sodium alginate, which has a high economic value, which also improves the feasible solution for the commercialization of RED salt difference power generation.

Claims

1. A method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy, characterized in that: The specific steps include: Step 1, preparing a sodium alginate solution; Step 2, preparing a graphene oxide solution; Step 3, placing the sodium alginate solution prepared in step 1 into the graphene oxide solution prepared in step 2, and fully dissolving it by electromagnetic stirring to obtain a mixed dispersion; Step 4, taking a polycarbonate membrane, placing the polycarbonate membrane as a substrate in a microfiltration bottle, taking the mixed dispersion in the microfiltration bottle for vacuum filtration, and obtaining a polycarbonate membrane covered with a graphene oxide sodium alginate composite membrane; Step 5: peeling off the graphene oxide sodium alginate composite membrane from the polycarbonate membrane covered with the graphene oxide sodium alginate composite membrane, and drying naturally to obtain the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy.

2. The method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy according to claim 1, characterized in that: The specific process of step 1 is as follows: Step 1.1, take deionized water into the reactor and take a certain amount of sodium alginate; Step 1.2, dissolving sodium alginate in deionized water, and fully dissolving it by electromagnetic stirring to obtain a sodium alginate solution.

3. The method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy according to claim 1, characterized in that: The concentration of the sodium alginate solution in step 1 is 1-20 mg / ml.

4. The method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy according to claim 1, characterized in that: The concentration of the graphene solution in step 1 is 0.1-5 mg / ml.

5. The method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy according to claim 1, characterized in that: The specific process of step 2 is: Step 2.1, taking a certain amount of graphene oxide into another reactor and taking deionized water; Step 2.2, adding deionized water to the graphene oxide for dilution to obtain a graphene oxide solution.

6. The method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy according to claim 1, characterized in that: The volume of the sodium alginate solution added in step 3 is not greater than the volume of the graphene oxide solution.

7. The method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy according to claim 1, characterized in that: The rotation speed of the electromagnetic stirring in step 3 is 800-1200 r / min, and the time of the electromagnetic stirring is 6-24 h.

8. The method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy according to claim 1, characterized in that: The vacuum filtration time in step 4 is 5-7 days.

9. The method for preparing a graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy according to claim 1, characterized in that: The natural drying time in step 5 is 8-24 hours.

10. Graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy, characterized in that: The invention is prepared by the method for preparing the graphene oxide sodium alginate composite membrane for extracting ocean osmotic energy as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method and application of graphene oxide / sodium alginate liquid crystal composite solution

    CN105237816A

  • Graphene oxide / sodium alginate composite nanofiltration membrane with controllable water flux or retention rate

    CN114887498A

  • Graphene oxide / chitosan composite nanofiltration membrane with controllable water flux or retention rate and application thereof

    CN114984757A

  • Preparation method and application of graphene oxide film with pH response and non-response conversion characteristic

    CN118988007A

Cited By

  • Nanofluid device and application thereof

    CN121288565A

  • Graphene oxide composite membrane capable of stimulating response as well as preparation method and application of graphene oxide composite membrane

    CN121401899A